Signal peptidase SpsB coordinates staphylococcal cell cycle, surface protein septal trafficking, and LTA synthesis - Ran Zhang; Yaosheng Jia; Salvatore J. Scaffidi; Jesper J. Madsen; Wenqi Yu (mBio)
ABSTRACT Cell wall-anchored surface proteins of Gram-positive bacteria, harboring a highly conserved YSIRK/G-S signal peptide (SPYSIRK+), are deposited at cell division septum and anchored to septal peptidoglycan. The mechanisms supporting YSIRK protein septal trafficking remain elusive. Previously, we identified that LtaS-mediated lipoteichoic acid (LTA) synthesis restricts septal trafficking of YSIRK+ proteins in Staphylococcus aureus. Interestingly, both LtaS and SPYSIRK+ are cleaved by the signal peptidase SpsB, but the biological implications remain unclear. Here, we show that SpsB is required for cleaving SPSpA(YSIRK+) of staphylococcal surface protein A (SpA). Depletion of spsB not only diminished SPSpA processing but also abolished SpA septal localization. The mis-localization is attributed to the cleavage activity of SpsB, as an A37P mutation of SPSpA that disrupted SpsB cleavage abrogated SpA septal localization. Strikingly, depletion of spsB led to aberrant cell morphology, cell cycle arrest, and daughter cell separation defects. Localization studies showed that SpsB was enriched at the septum of dividing staphylococcal cells. Finally, we show that SpsB spatially regulates LtaS as spsB depletion enriched LtaS at the septum. Collectively, the data suggest a new dual-mechanism model mediated by SpsB: the abundant YSIRK+ proteins are efficiently processed by septal localized SpsB; SpsB cleaves LtaS at the septum, which spatially regulates LtaS activity contributing to YSIRK+ proteins septal trafficking. The study identifies SpsB as a novel and key regulator orchestrating protein secretion, cell cycle, and cell envelope biogenesis.IMPORTANCESurface proteins containing a YSIRK/G-S-positive signal peptide are widely distributed in Gram-positive bacteria and play essential roles in bacterial pathogenesis. They are highly expressed proteins that are enriched at the septum during cell division. The biogenesis of these proteins is coordinated with cell cycle and LTA synthesis. The current study identified the staphylococcal signal peptidase SpsB as a key determinant in regulating surface protein septal trafficking. Furthermore, this study highlights the novel functions of SpsB in coordinating LtaS-mediated LTA production and regulating staphylococcal cell cycle. As SpsB, YSIRK+ proteins, and LTA synthesis are widely distributed and conserved, the mechanisms identified here may be shared across Gram-positive bacteria.